2014
DOI: 10.1089/pho.2013.3573
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Er,Cr:YSGG Laser-Assisted Treatment of Teeth with Apical Periodontitis: A Blind Randomized Clinical Trial

Abstract: The present findings suggest that for single-rooted and premolar teeth, this laser-assisted protocol can achieve predictable endodontic outcomes, comparable to conventional strategies in 1 year of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
1
21
0
2
Order By: Relevance
“…In the present case report, and in similarity with the available clinical data [104,105,110], the use of a resin-based sealer (Topseal, Dentsply-Maillefer) has demonstrated high affinity for dentin penetration and hermetic seal.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the present case report, and in similarity with the available clinical data [104,105,110], the use of a resin-based sealer (Topseal, Dentsply-Maillefer) has demonstrated high affinity for dentin penetration and hermetic seal.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast with the previous reports using RFT in straight canals of the anterior teeth [104,110], the RFT used in these two clinical cases were moved in a spiralling motion along the root canal walls. The aim was to facilitate the fibre withdrawing motion and to possibly overcome any ledging that may occur in apical thirds of curved canals.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The removal of biofilm from the inner walls of the canal is further enhanced when irrigation is assisted by ultrasonic or laser activation [32, 33]. However, several clinical studies have shown no significant clinical advantage of these procedures over conventional protocols [3436] and the extent in which they affect biofilms located in remote regions of oval-shaped canals, lateral canals and tubules, is still unknown [37]. Hence, intracanal medicaments are inserted into root canals intending to restrict bacterial regrowth and supply continued disinfection [38].…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the outcome of using an Er,Cr:YSGG laser with a radial firing tip (RFT) that can ensure uniform intracanal illumination. The investigators compared the laser technique vs conventional use of 3% sodium hypochlorite and interim calcium hydroxide paste in teeth with chronic apical periodontitis (Martins et al., ). The laser protocol included RFT2 (tip length 25 mm, fiber outer diameter 275 μm, 140 μs, 37.5 mJ, 20 Hz) and RFT3 (tip length 21 mm, fiber outer diameter 415 μm, 140 μs, 62.5 mJ, 20 Hz) at the first and second appointments respectively, four times each, moving at 2 mm/s from apical to coronal direction.…”
Section: Photodynamic Therapy In Oral Diseasesmentioning
confidence: 99%